Electrochemical Ammonia: Power to Ammonia Ratio and Balance of Plant Requirements for Two Different Electrolysis Approaches - Allen, Jessica; Panquet, Sebastien; Bastiani, Adrian (Frontiers in Chemical Engineering, 2021)
Electrochemical ammonia generation allows direct, low pressure synthesis of ammonia as an alternative to the established Haber-Bosch process. The increasing need to drive industry with renewable electricity central to decarbonisation and electrochemical ammonia synthesis offers a possible efficient and low emission route for this increasingly important chemical. It also provides a potential route for more distributed and small-scale ammonia synthesis with a reduced production footprint. Electrochemical ammonia synthesis is still early stage but has seen recent acceleration in fundamental understanding. In this work, two different ammonia electrolysis systems are considered. Balance of plant (BOP) requirements are presented and modelled to compare performance and determine trade-offs. The first option (water fed cell) uses direct ammonia synthesis from water and air. The second (hydrogen-fed cell), involves a two-step electrolysis approach firstly producing hydrogen followed by electrochemical ammonia generation. Results indicate that the water fed approach shows the most promise in achieving low energy demand for direct electrochemical ammonia generation. Breaking the reaction into two steps for the hydrogen fed approach introduces a source of inefficiency which is not overcome by reduced BOP energy demands, and will only be an attractive pathway for reactors which promise both high efficiency and increased ammonia formation rate compared to water fed cells. The most optimised scenario investigated here with 90% faradaic efficiency (FE) and 1.5 V cell potential (75% nitrogen utilisation) gives a power to ammonia value of 15 kWh/kg NH3 for a water fed cell. For the best hydrogen fed arrangement, the requirement is 19 kWh/kg NH3. This is achieved with 0.5 V cell potential and 75% utilisation of both hydrogen and nitrogen (90% FE). Modelling demonstrated that balance of plant requirements for electrochemical ammonia are significant. Electrochemical energy inputs dominate energy requirements at low FE, however in cases of high FE the BOP accounts for approximately 50% of the total energy demand, mostly from ammonia separation requirements. In the hydrogen fed cell arrangement, it was also demonstrated that recycle of unconverted hydrogen is essential for efficient operation, even in the case where this increases BOP energy inputs.